(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Expansion of business and cultural relations with foreign countries determines new requirements for language education. One of the conditions for successful and complete communication is the skill of listening. The development of this skill, starting on the initial stage of language learning, promotes the formation of communicative competence. The present study focuses on one of the most urgent problems of modern methodology of foreign language teaching in higher education – teaching students foreign language communication based on listening. The basis for the future full communication in a foreign language is a process of successful formation of skills of perception, recognition and understanding of speech in language study. The material for listening serves as a model of real language environment that allows students to engage in speech activity. Audiovisual materials provide a visual representation of a situation and allow seeing the articulation of spoken sounds, which facilitates the processes of perception and understanding of foreign speech.